2019
DOI: 10.1080/10220461.2019.1702091
|View full text |Cite
|
Sign up to set email alerts
|

Africa and the G20: A relational view of African agency in global governance

Abstract: An analysis of the Group of 20 (G20) agenda with reference to Africa reveals that the region has received mixed attention across presidencies, underpinned by broad partnership initiatives such as the G20 Africa Partnership (Hamburg Summit). Calling for enhanced and concretised African engagement in G20 processes, this article analyses the potential collective agency of Africa in the G20 shaped by interactions with a range of actors, processes and the specific political and historical contexts that have framed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…According to metrocentrism (Go, 2016), 1 Africa's modern history of being exploited, marginalised, victimised, and silenced places it on the margins/peripheries of international (global) politics. The continent's colonial past has led to its portrayal as a passive actor and minor player vis-à-vis the main forces of change in international politics (Mabera, 2019) and to its characterisation as lacking agency. Simultaneously, the limited agency of Africa in IR has warranted phrases such as "representational deficiency" and "epistemic repression."…”
Section: Sources Of Constraints On Africa's Agency In Global Politicsmentioning
confidence: 99%
“…According to metrocentrism (Go, 2016), 1 Africa's modern history of being exploited, marginalised, victimised, and silenced places it on the margins/peripheries of international (global) politics. The continent's colonial past has led to its portrayal as a passive actor and minor player vis-à-vis the main forces of change in international politics (Mabera, 2019) and to its characterisation as lacking agency. Simultaneously, the limited agency of Africa in IR has warranted phrases such as "representational deficiency" and "epistemic repression."…”
Section: Sources Of Constraints On Africa's Agency In Global Politicsmentioning
confidence: 99%
“…Thereafter, Slaughter (2019a) assembled a range of international relations (IR) perspectives on the G20 and in the process demonstrated that edited volumes can be consistent in the focus and quality of their contributions. Coinciding with the Saudi assumption of the G20 presidency in 2020, a special issue of the South African Journal of International Affairs took stock of the ten-year summit process and explored what it has become, how it might be reformed, how it engages with a range of non-state actors, and the role of rising powers (Benson and Zürn 2019;Berger et al 2019;Brandi 2019;Cooper 2019;He 2019;Kaul 2019;Luckhurst 2019a;Mabera 2019;Parlar Dal and Dipama 2019;Villanueva Ulfgard and Vega 2019). Inevitably, however, the discussion regularly returns to the issues highlighted by Subacchi: 'Legitimacy, effectiveness and accountability are the three key points in any discussion of the Group of 20 … [and a] lack of legitimacy is the G20's original sin ' (2019, 703).…”
Section: Introductionmentioning
confidence: 99%